Heat hardening enhances metabolite-driven thermoprotection in the Mediterranean mussel Mytilus galloprovincialis - Georgoulis, Ioannis; Bock, Christian; Lannig, Gisela; Pörtner, Hans O.; Sokolova, Inna M.; Feidantsis, Konstantinos; Giantsis, Ioannis A.; Michaelidis, Basile (Frontiers in Physiology, 2023)
Temperature affects organisms' metabolism and ecological performance. Owing to climate change, sea warming constituting a severe source of environmental stress for marine organisms, since it increases at alarming rates. Rapid warming can exceed resilience of marine organisms leading to fitness loss and mortality. However, organisms can improve their thermal tolerance when briefly exposed to sublethal thermal stress (heat hardening), thus generating heat tolerant phenotypes. We investigated the "stress memory" effect caused by heat hardening on M. galloprovincialis metabolite profile of in order to identify the underlying biochemical mechanisms, which enhance mussels' thermal tolerance. The heat hardening led to accumulation of amino acids (e.g. leucine, isoleucine and valine), including osmolytes and cytoprotective agents with antioxidant and anti-inflammatory properties that can contribute to thermal protection of the mussels. Moreover, proteolysis was inhibited and protein turnover regulated by the heat hardening. Heat stress alters the metabolic profile of heat stressed mussels, benefiting the heat-hardened individuals in increasing their heat tolerance compared to the nonheat-hardened ones. These findings provide new insights in the metabolic mechanisms that may reinforce mussels' tolerance against thermal stress providing both natural protection and potential manipulative tools (e.g. in aquaculture) against the devastating climate change effects on marine organisms.